Penerapan Corporate Social Responsibility Pada Perusahaan Di Indonesia Khususnya Di Sektor Bisnis - Atiningsih, Suci (STIE Surakarta, 2012)
This study objective to determine the application of CSR in companies in Indonesia, the factors that affect the application of CSR and its implications on the business sector. This is a type of descriptive qualitative research which describes and analyzes the implementation of CSR in companies in Indonesia and its implications in the business sector. This study uses secondary data including data on the implementation of CSR is compiled from various sources of literature. Technical analysis of the data using the flow of data collection activities, interpret, and ends with a conclusion.This study shows CSR in Indonesia implemented by many large companies both private and state-owned (SOE), but most still view CSR as charity or charitable activities rather than as a long-term corporate strategy. Motivation to implement more CSR as social-spiritual motives. implementation of CSR is determined by the value of the companys internal corporate leadership, especially the decision. External factors that government regulation into the factors that determine the CSR after the Indonesian government in 2007 set the Limited Liability Company Act, which requires CSR for companies dealing in natural resources. This rule invites the agree and disagree of the substance of CSR: voluntary or mandatory. The argument is a social problem or public interest is not a realm of responsibility of business organizations, but the responsibility of the public sector (state). Implementing CSR should be left entirely in the business sector or the third sector.